Delamanid in the Treatment of MDR/pre-XDR TB in Arkhangelsk Region in 2019–2021 - E. S. Khimova; D. V. Perkhin; O. M. Sveshnikova; S. V. Makhmaeva; V. N. Verkhovaya; P. I. Eliseev; E. I. Nikishova; A. O. Maryandyshev (Туберкулез и болезни лёгких)
The objective: to evaluate the efficacy and safety of delamanid in a short-course treatment regimen for patients with MDR/pre-XDR pulmonary tuberculosis in Arkhangelsk Region from 2019 to 2021.Subjects and Methods. 32 patients (4 with MDR TB and 28 with pre-XDR TB) started treatment with delamanid within the combination chemotherapy with new drugs, treatment lasted for 12 months. All patients with pre-XDR TB received delamanid, bedaquiline, linezolid, and clofazimine, then the chemotherapy regimen was compiled depending on the clinical situation.Results. Effective treatment was registered in 21/32 patients (65,6%). 4/32 (12,5%) patients interrupted the treatment. Treatment failure was registered in 2/32 (6,25%). During the study, 5 (15,6%) patients died, in none of them tuberculosis was the cause of death. 106 adverse events (AEs) were reported, they included electrolyte imbalance (18,9%), hepatotoxic (16,0%), nephrotoxic (10,4%) and cardiotoxic (10,4%) reactions.